The Determinants of Banks' Liquidity Buffers in Central America - Delechat, Corinne; Henao Arbelaez, Camila; Muthoora, Priscilla; Vtyurina, Svetlana (Washington, D.C. : International Monetary Fund, 2012)
Banks' liquidity holdings are comfortably above legal or prudential requirements in most Central American countries. While good for financial stability, high systemic liquidity may nonetheless hinder monetary policy transmission and financial markets development. Using a panel of about 100 commercial banks from the region, we find that the demand for precautionary liquidity buffers is associated with measures of bank size, profitability, capitalization, and financial development. Deposit dollarization is also associated with higher liquidity, reinforcing the monetary policy and market development challenges in highly dollarized economies. Improvements in supervision and measures to promote dedollarization, including developing local currency capital markets, would help enhance financial systems' efficiency and promote intermediation in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet